STRATEGI KOMUNIKASI KELOMPOK DAKWAH ISTIQOMAH HIJRAH RANTAUPRAPAT DALAM MENUMBUHKAN KECINTAAN MASYARAKAT TERHADAP MASJID - Reihan Reihan (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2024)
The background of this research is that mosques today are often seen merely as ordinary public buildings, frequented mostly by elderly individuals. In contrast, during the time of the Prophet Muhammad, mosques served not only as places for congregational prayers but also as centers for various community activities. The Istiqomah Hijrah Da'wah Group is one of the youth-led Islamic outreach groups in Rantauprapat that engages in numerous religious activities, including visiting mosques outside the city and organizing activities within mosques. The aim of this study is to understand and analyze the communication strategies employed by the Istiqomah Hijrah Da'wah Group in fostering community love and appreciation for mosques. This research utilizes a qualitative approach with descriptive qualitative methods. Key informants include pivotal figures within the group such as the chairman, secretary, and other members of the Istiqomah Hijrah Da'wah Group. Data collection methods include participant observation, structured and unstructured interviews, as well as documentation through photos and videos. Data analysis involves data classification, reduction, description, and drawing conclusions, supported by data validity through source, method, and time triangulation. The findings reveal that the Istiqomah Hijrah Da'wah Group employs persuasive communication to encourage community involvement in mosques, as well as educational communication through weekly study sessions and biennial religious tours. They also utilize social media platforms like WhatsApp and Facebook to disseminate information about activities and messages related to mosques. Through these strategies, the group aims to strengthen the role of mosques in modern society.